Perancangan Brand dan Identity Es Kacang Merah Top Ternate (Es KTT) Malang - Christanto Putra (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2021)
Brand is one important aspect for a business. Brand can be used as differentiation and also as the identity of the business. This make their business famous and people know about their business. One business that is growing in Malang is Es KTT. The writer see some problem that Es KTT deals that is Es KTT doesn’t have strong branding, so many people still don’t know about it and it doesn’t have maximum development. So this design brand and identity made with qualitative method. The data analyzed using SWOT, combined with brand roadmap method by Mike Moser. Then using cyclic strategy, and all of it resulted brand visualitation concept and the identity in the form of logo and the use of it in any media that Es KTT need, so Es KTT can attract people’s attention and interest. The result of this research has been surveyed to 50 people and they said they are satisfied with the result.